Towards an efficient city: the case of Santiago, Chile - Melo, Pedro (Estudios de Economía, 2016)
Cities are the outcome of processes of economic maximization where not all requirements of perfect competition are given (there are externalities, transaction and information costs, and market power), and where the past does have a bearing. “Real” prices of public services and especially of transport are essential to achieve an efficient city. When differential costs by location are not adequately charged and there are externalities not internalized, regulations for city size and stable administrative restrictions on land use can correspond to an economically sustained solution, of the “second best” type. Government policies and actions regarding housing are not neutral to a city’s efficiency. These elements are analyzed from the outlook of the facts that seem to stem from the evolution experienced by Chile’s capital city over the last 50 years.